The relationship between collection availability and reader interest in reading in the SMA Negeri 8 OKU Library - Fatmawati, Ari; Istiarni, Atin (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
Libraries can function as a means of reading. Libraries must be able to foster interest in reading through their collections. However, it is very unfortunate that libraries, which play an important role in fostering children's interest in reading, are in poor condition. Therefore, this research aims to find out how the availability of library collections impacts students' interest in reading at SMA Negeri 8 OKU, South Sumatra. So, there are several ways to find out collection availability and reading interest. Relevance, user orientation, completeness, and up-to-date collections are part of collection availability. However, reading interest can be measured through reading pleasure, frequency of books read, and awareness of reading the book. This research is quantitative research that uses explanatory methods. Based on the research results, it can be concluded that there is a significant influence of the availability of library collections on students' interest in reading at SMA Negeri 8 OKU, South Sumatra. This is indicated by a significance value < 0.05 or 0.000 < 0.05 with a calculated f of 153.350 which means it is greater than the f table of 2.70 with a value of the significance level smaller than 0.05, so the real availability of the Collection (Variable) influences reading interest (Variable Y). Besides that, it can also be concluded that the variable availability of collections has an influence and can be used to predict reading interest.